Respuesta :
Answer:
-1
Step-by-step explanation:
For a line joining two points (x1, y1) and (x2, y2), it's slope is given as:
[tex] \boxed{ \mathsf{slope = \frac{ y_{2} -y _{1}}{ x_{2} - x _{1}} }}[/tex]
Here, the two points are (-1, 6) and (2, 3) in place of (x1, y1) and (x2, y2).
Solving for slope:
[tex] \implies \mathsf{ \frac{3 - 6}{2 - ( -1 )} }[/tex]
[tex] \implies \mathsf{ \frac{ - 3}{2 + 1 } }[/tex]
[tex] \implies \mathsf{ \frac{ - 3}{3 } }[/tex]
[tex] \implies \mathsf{ - 1 }[/tex]
Hence, the slope of the line joining the given points is -1.